Transformasi Pembelajaran PAI di Era Digital: Integrasi Teknologi dalam Desain Pembelajaran - Aprina Noor Latifah; Ani Cahyadi (Yayasan Al-Afif, 2026)
Digital transformation in the era of the Industrial Revolution 4.0 presents both opportunities and challenges for Islamic Religious Education (IRE). The main issue lies in the use of technology that is not yet fully aligned with Islamic ethical and spiritual values. This study examines the integration of technology in the instructional design of IRE while maintaining consistency with religious principles. This qualitative study employs a literature review by analyzing journal articles, academic books, and relevant digital sources. The findings show that e-learning, Learning Management Systems (LMS), Islamic interactive media, virtual classes, hybrid learning, and artificial intelligence (AI) enhance flexibility, effectiveness, and learning access. However, challenges include the risk of content deviation, digital ethical issues, data security concerns, and reduced direct interaction between teachers and students. Eventually, technology integration in IRE must be accompanied by strengthened digital literacy, ethical media practices, and the role of teachers in guiding students’ character development.